EXPANSION OF THE PRODUCT RANGE AS A TOOL FOR INCREASING THE SALES FUNNEL IN THE MANUFACTURING SECTOR - Sanahurskyi, Yurii (Global Prosperity, 2023)
Abstract. Modern manufacturing enterprises face constant pressure from growing competition and rapidly changing customer expectations. In these conditions, broadening the product range should be viewed as a strategic choice rather than a secondary marketing move. Expanding the assortment directly influences how the sales funnel functions: it determines the size of the initial audience, the ease of guiding clients through subsequent stages, and the strength of long-term retention. The article explores the role of assortment policy in shaping the funnel, with particular attention to the relationship between product variety and conversion rates. Attention is also given to the challenges of balancing diversification with production capacity, since offering more options is effective only when supported by operational efficiency. Examples drawn from machinery, food manufacturing, building materials, and clothing industries show that diversified product lines allow companies to reach new customer groups, accelerate purchasing decisions, and foster repeat demand. The study concludes that assortment expansion not only widens market coverage but also enhances resilience to demand fluctuations, supports innovation within the enterprise, and strengthens overall competitiveness. As a result, assortment strategy emerges as a crucial long-term asset for manufacturers aiming at sustainable growth..